2021
DOI: 10.1093/neuonc/noab075
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CSF1/CSF1R axis is a potential treatment strategy for malignant meningiomas

Abstract: Background Malignant meningiomas are fatal and lack effective therapy. As M2 macrophages are the most prevalent immune cell type in human meningiomas, we hypothesized that normalizing this immunosuppressive population would be an effective treatment strategy. Methods We used CIBERSORTX to examine the proportions of 22 immune subsets in human meningiomas. We targeted the colony stimulating factor 1 (CSF1) or CSF1 receptor (CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Recent studies suggest that targeting the immune microenvironment may be a promising strategy for meningiomas [6][7][8][9][10][11][12] . Genomic-characterization studies suggest that a subset of highgrade meningiomas possess a high somatic mutation burden 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that targeting the immune microenvironment may be a promising strategy for meningiomas [6][7][8][9][10][11][12] . Genomic-characterization studies suggest that a subset of highgrade meningiomas possess a high somatic mutation burden 9 .…”
mentioning
confidence: 99%
“…We found a decrease in CD4+ and CD8+ T cells, an increase in the number of FOXP3-expressing immunoregulatory (Treg) cells, and an increase in programmed deathligand-1 (PD-L1) expression on tumor cells, compared with grade-1 meningiomas 14 . Others have identified that the presence of immunosuppressive myeloid cells in high-grade meningioma 11,12 , linked PD-L1/PD-L2 expression with worse outcomes 10,12 , and found enrichment of PD-1/PD-L1 signaling in malignant meningiomas by single-cell RNA sequencing 11 .…”
mentioning
confidence: 99%
“…Controversially, elevated CSF1 expression levels have been associated with an unfavorable outcome in various tumor diseases 30–33 . Along these lines, a recent study found elevated levels of CSF1 in the plasma of meningioma patients, a correlation of CSF1 expression and an increased number of infiltrating macrophages of an anti-inflammatory phenotype, and a beneficial effect of CSF1/CSF1R targeting antibody treatment in a meningioma mouse model 34 .…”
Section: Discussionmentioning
confidence: 94%
“…Mechanisms of meningioma progression were confirmed using later models, wherein Nf2 inactivation in synergy with homozygous or heterozygous Cdkn2ab deletions led to increased meningioma frequency and induced grade II and III meningiomas, thus representing a reliable atypical or anaplastic model that mimics the human pathology [59]. These models also offer the possibility of producing meningioma cell lines from mouse tumors and syngeneic orthotopic allografts to immunocompetent wildtype mice, which represent the closest models of sporadic malignant meningiomas [75].…”
Section: Cre-loxp Systemmentioning
confidence: 89%